COMPARISON OF MALAYSIAN DESIGNERS' CLOTHES FOR THE EID FESTIVAL IN 2023 - Suriati Saidan; Wan Nadhra Ixora Wan Kamarulbaharin; Husna Saaidin; Norzaleha Zainun; Mohd Hafnidzam Adzmi, (JOURNAL OF TOURISM, HOSPITALITY AND ENVIRONMENT MANAGEMENT (JTHEM), 2024)
Fashion design nowadays is a fashion trend that is the best alternative for Muslim women who want to cover their aura with an attractive style. With various options, Islamic clothing is not considered conservative or outdated. Therefore, fashion design should be more contemporary, following the Islamic characteristics of a Muslim, and suitable for use by all nations. In this paper, the researcher will look at the fashion used in the design production of the trends Eid Festival for 2022-2023. Fashion trends are an essential element in determining the concept of clothing design. As a trend of the forecasting concept, several things significantly impact the fashion industry. Forecasting fashion, technology, and cultural trends is a critical part of the marketing business committed to recognizing consumer behaviour patterns and assisting organizations and brands in connecting with consumers. It will impact popularity and lifestyle through the choice of colours and fabrics. It necessitates scientific knowledge as well as creative thinking. Thus, fashion forecasting is a branch of the fashion industry concerned with predicting future fashion trends regarding colours, design techniques, textile materials, and other factors influencing consumer demand.